A framework for continuous improvement of the IT acquisition process at Brazilian federal public organisations: an action-research study. (23rd June 2022) - Santos, Melquizedequi Cabral Dos; Santos, Wylliams Barbosa; Oliveira, Sandro Ronaldo Bezerra; Vasconcelos, Alexandre Marcos Lins De; Silva, Carla
Information technology acquisition (ITA) is essential to support activities and processes in public and private organisations. In the context of Federal Public Organizations (FPO) in Brazil, the existent norms possess limitations regarding a continuous improvement to the ITA process. The objective of this article is to develop a specific framework that offers support to the managers when they optimise the ITA process, aiming to support them in understanding, managing, and implementing continuous improvement. To reach this objective, three action-research cycles were performed, involving numerous data collections, interventions and improvements. The framework was successfully implanted at a typical public educational organisation, providing benefits such as improvement in satisfaction on the part of stakeholders; reduction in the rate of flaws, return, and rework; better adherence to the ITA process and improvement in the quality of the ITA process.